Investigation on the effect of tea polyphenol extracts to digestion properties. - Abdullah, Uthumporn Utra @ Sapina (Universiti Sains Malaysia, 2016)
This research is conducted to determine antioxidant activity in different types of tea [black tea (8T), oolong tea (OT), green tea (GT), spent black tea (S8T), spent oolong tea (SOT) and spent green tea (SGT)] and to study the effect on polyphenols on digestion enzymes. Gallic acid, caffeine and four catechins (catechin, gallocatechin, epicatechin and epigallocatechin) were analyzed and quantified by using HPLC. Investigation on the hypoglycemic effect of those teas using suitable in vitro methods and developing biscuits incorporated with 8T and SST and to evaluate the effect on nutritional compositions, texture profile, color, sensorial acceptability and glycemic index (GI) value. GT obtained the highest TPC, TFC and antioxidant activity followed by oolong and black tea. The analytical HPLC results obtained also indicated that GT contained significantly higher amount of catechins than OT, 8T, SGT, SOT and SBT. However, BT showed significantly higher glucose adsorption capacity than S8T, and others samples and all samples exhibited significant reduction in glucose diffusion and amylolysis kinetics studies compared to control. 8T inhibited the highest alpha-amylase and apha-glucosidase activity in a dose dependent manner. From in vitro amylolysis kinetics, BT and SST incorporated biscuit found significantly reduced glucose release compared to control biscuit.